New cytotoxic compounds from the leaves of Caesalpinia benthamiana (Baill.) Herend. & Zarucchi (Fabaceae) - Taiwo ELUFIOYE; Tayo FAMOJURO; Olumayokun Olajide; Michael Dybek; Adeboye Adejare (Mashhad University of Medical Sciences, 2021)
Objective: The incidence of multi-drug resistant cancer and the adverse effects associated with available chemotherapy have necessitated the search for new drug candidates. This study investigates the cytotoxic activity of Caesalpinia benthamiana. Materials and Methods: Column chromatography (CC) and preparative thin layer chromatography (PTLC) were used to isolate compounds. Structural elucidation was done by spectroscopic analysis. MTT assay was used to evaluate cytotoxicity of the compounds against three human adenocarcinoma cells, using methotrexate and dimethyl sulfoxide (DMSO) as positive and negative controls, respectively. CyQuant direct cell proliferation and caspase-3/7 green detection assays were used to investigate the dichloromethane fraction. IC50 values of isolated compounds were determined from sigmoidal dose-response curve. Results: Four new cytotoxic compounds, benthamianoate (2), benthamiacone (3), benthamianin (5) and benthamianol (6), and two known compounds, methyl gallate (1) and 2-methoxyacrylic acid (4) were identified. All the compounds were active with the new monoterpenoid characterized as benthamiacone exhibiting the highest activity (IC50 13.23-21.97 μg/ml) across cancer cell lines investigated. CyQuant direct cell proliferation assay showed significant reduction in the number of live carcinoma cells, while caspase-3/7 green detection assay showed significant increase in the number of dead carcinoma cells. Conclusion: This study revealed potential cytotoxic compounds which are here reported for the first time from C. benthamiana.